The Influence of Digital Transformation on Organizational Performance in Tokopedia Startup in Indonesia - Muhammad Ridwan; Farah AlFanur (Eduvest - Journal of Universal Studies, 2025)
Global business dynamics in the digital era require fundamental organizational transformation to stay competitive and sustain performance. Organizational performance—measured by operational efficiency, innovation capability, and customer satisfaction—is a critical success indicator, especially for technology-driven startups. The Indonesian e-commerce sector has grown significantly, propelled by higher internet penetration, altered consumer behavior, and digital innovations from various platforms. This study examines the influence of digital transformation on organizational performance in Tokopedia startups in Indonesia, focusing on technological adoption's effects on operational efficiency, customer experience, and business outcomes. Tokopedia, known for its marketplace model, supports MSMEs and offers diverse services facilitating sellers and buyers. Using qualitative methods with in-depth interviews of MSME actors, employees, and customers, this research defines variables and indicators, employing open-ended questions to capture respondent perspectives. Interview data analyzed with NVivo software reveal that digital transformation improves performance, notably in ordering efficiency and payment speed. However, resource constraints and data security challenges remain barriers needing attention. The study recommends that other tech startups invest in infrastructure and training to maximize digital transformation benefits. This approach highlights how digital technology adoption can significantly impact organizational success in Indonesia's fast-growing e-commerce